2020
DOI: 10.1016/j.jaccas.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of an Azygos Vein Varix With a Covered Stent

Abstract: An azygos vein varix was incidentally discovered in a 26-year-old man. Owing to the potential risk of pulmonary emboli, we implanted a covered stent in the superior vena cava, effectively excluding the varix. Eighth months later, the varix was thrombosed and involuted. ( Level of Difficulty: Advanced. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Summarizing the previously reported cases, most of the patients were asymptomatic or had their AVA discovered incidentally on physical examination for other reasons. Among the common symptoms in patients, 13 patients had chest pain [ 12 15 , 17 , 18 , 20 , 22 , 26 , 35 , 44 , 48 , 60 ], 10 patients had chest tightness and even dyspnea [ 3 , 6 , 19 21 , 23 , 25 , 45 ], 4 patients had cough [ 3 , 9 , 43 , 53 ], 3 patients had symptoms of dysphagia [ 19 , 43 , 59 ], and 3 patients' AVAs were accidentally discovered in trauma [ 3 , 11 ]. Contrast-enhanced CT and magnetic resonance imaging (MRI) are the main noninvasive methods for the diagnosis of AVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarizing the previously reported cases, most of the patients were asymptomatic or had their AVA discovered incidentally on physical examination for other reasons. Among the common symptoms in patients, 13 patients had chest pain [ 12 15 , 17 , 18 , 20 , 22 , 26 , 35 , 44 , 48 , 60 ], 10 patients had chest tightness and even dyspnea [ 3 , 6 , 19 21 , 23 , 25 , 45 ], 4 patients had cough [ 3 , 9 , 43 , 53 ], 3 patients had symptoms of dysphagia [ 19 , 43 , 59 ], and 3 patients' AVAs were accidentally discovered in trauma [ 3 , 11 ]. Contrast-enhanced CT and magnetic resonance imaging (MRI) are the main noninvasive methods for the diagnosis of AVA.…”
Section: Discussionmentioning
confidence: 99%
“…However, poor tumor enhancement or intratumoral thrombus formation in the AVA may lead to misdiagnosis of AVA as a solid tumor or mediastinal lymphadenopathy [ 24 ]. When a mediastinal mass does not exclude the diagnosis of azygosmosis, needle biopsy is not recommended because of the risk of massive bleeding [ 25 , 26 ]. In the present case, the three-dimensional reconstruction of the patient showed that the tumor was located in the AV, and the tumor was connected with the superior vena cava and the AV, which confirmed the diagnosis of AVA.…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing the previously reported cases, most of the patients were asymptomatic or had their AVA discovered incidentally on physical examination for other reasons. Among the common symptoms in patients, 13 patients had chest pain [9][10][11][12][14][15]17,19,23,34,43,47,59] , 10 patients had chest tightness and even dyspnea [2][3][16][17][18]20,22,44] , 4 patients had cough [2,6,42,52] , 3 patients had symptoms of dysphagia [16,42,58] , and 3 patients' AVAs were accidentally discovered in trauma [2,8] . Contrast-enhanced CT and magnetic resonance imaging (MRI) are the main noninvasive methods for the diagnosis of AVA.…”
Section: Discussionmentioning
confidence: 99%
“…However, poor tumor enhancement or intratumoral thrombus formation in the AVA may lead to misdiagnosis of AVA as a solid tumor or mediastinal lymphadenopathy [21] . When a mediastinal mass does not exclude the diagnosis of azygosmosis, needle biopsy is not recommended because of the risk of massive bleeding [22][23] . In the present case, the three-dimensional reconstruction of the patient showed that the tumor was located in the AV, and the tumor was connected with the superior vena cava and the AV, which con rmed the diagnosis of AVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation